Zimbardo's “Stanford Prison Experiment” and the relevance of social psychology for teaching business ethics - Brady, F. Neil (Journal of business ethics, 1988)
The prevailing pedagogical approach in business ethics generally underestimates or even ignores the powerful influences of situational factors on ethical analysis and decision-making. This is due largely to the predominance of philosophy-oriented teaching materials. Social psychology offers relevant concepts and experiments that can broaden pedagogy to help students understand more fully the influence of situational contexts and role expectations in ethical analysis. Zimbardo's “Stanford Prison Experiment” is used to illustrate the relevance of social psychology experiments for business ethics instruction.